EVALUASI DAN PERENCANAAN LAJU VOLUME SERTA DIMENSI CEROBONG TERHADAP POLA SEBARAN EMISI DARI CEROBONG INDUSTRI SEMEN DI TARJUN: Muhammad Alif Azhar, Eva Ariani dan Riza Miftahul Khair - muhammad alif azhar; Riza Miftahul Khair; Rony Riduan; Gusti Ihda Mazaya (Prodi Teknik Lingkungan Fakultas Teknik Universitas Lambung Mangkurat, 2025)
ABSTRACT Management and control of an air pollution is needed for the impact of air pollution is not very severe. The cement industry is one of the industries that uses high temperature heating in the production process. Mass balance calculations are needed to see the amount of material entering and leaving a process, based on the law of conservation of mass, that is, the amount of mass that enters is equal to the amount of mass that leaves. One source of immovable emissions is the chimney. Evaluation of the chimney dimensions is also carried out so that it can be a reference in the optimal exhaust gas velocity. Things to consider in analyzing an air quality using an analysis of the pollutant dispersion model. An application that can be used to predict the distribution of pollutants is AERMOD. The total mass entering the Suspension Preheater is 748,682.78 kg/hour. with a total mass output of 157,506,6898 kg/hour and a total mass loss of 591,176.09 kg/hour; Based on calculations to plan the volume and dimensions of the chimney by taking into account the conditions around the source point, the height of the chimney is 72 meters and 65 meters. With exhaust gas velocity is 20 m/s and 21 m/s, respectively; Based on the distribution pattern with a period of 24 hours, it is known that the concentration of TSP, SO2, and NO2 in the air when the receiving point is at an altitude of 1.5 meters from the ground surface has a maximum concentration of TSP, SO2, and NO2 respectively of 8,323 g/ m3, 36,171 g/m3, and 38,307 g/m3. While the difference between the simulated and in the field is better with a chimney height of 72 meters in order to maximize emission distribution compared to a chimney height of 65 meters.